The implementation of the oral history archives technique in social studies to foster pride in their national identity and values among Omani youth: a reflection of Oman vision 2040 - Al Hooti, Ameera (Atlanti, 2023)
Purpose: This study addresses the challenges faced by modern societies, with a specific focus on Oman and its educational foundation aligned with ‚Oman Vision 2040.‘ The primary objective is to assess the use of oral history archives in teaching social studies, exploring teachers‘ perceptions, familiarity, and the effectiveness of this approach in enhancing Omani students‘ identity and national values. Method/approach: The research employs purposeful sampling, incorporating focus group discussions, interviews, observation notes, and survey questionnaires. Thematic analysis is utilized to examine gathered data, categorizing findings into three themes: social studies teachers‘ views on oral history archives, their familiarity, and the efficacy of using this approach to enhance Omani students‘ identity and national values. Results: The research reveals positive perceptions among social studies teachers regarding the effectiveness of oral history archives as a teaching approach. Themes include teachers‘ perspectives, familiarity with the method, and the efficacy of using oral history to enhance identity and national values among Omani students. Conclusion/findings: The study emphasizes the importance of integrating oral history archives into the educational system, aligning with Oman Vision 2040‘s goals. Teachers perceive oral history archives as effective tools, enhancing student engagement, intellectual development, and contributing to the learning environment. Recommendations include institutional support, resource allocation, and training initiatives to promote successful implementation in classrooms. The study contributes to Oman‘s educational landscape and aligns with global oral history movements, emphasizing collaboration with international organizations for enhanced research methodologies and effective teaching techniques.
Keywords: archivio di storia orale; arhiv ustnega izročila; insegnanti di studi sociali; novejša zgodovina; Oman Vision 2040; omanska vizija 2040; oral history archive; recent history; social studies teachers; storia recente; učitelji družbenih ved